Container theme gardens : 42 combinations, each using 5 perfectly matched plants - Ondra, Nancy J. (Storey Publishing, 2016)
Ondra shows you how to choose a container and a five-plant theme, and use them to create a beautiful combination for any season, situation, or taste. She shows you how to choose the color scheme, arrangement, and container that will fit your style.